Information behaviour in the customer-focused small manufacturing company - Martin, Valerie Ann (Cranfield University, 2000)
This thesis explores the nature and management of information in customer focused small manufacturing companies. Small manufacturing companies (SMCs) face increasingly changing and wider customer demands. They are often power cultures, with informal information and communication flows. Informal information is no longer enough in the face of growing complexity. Formal information is often about co-ordinating processes, for example, BS EN ISO quality standards, or simply recording customer information instead of relying on memory. Academic approaches to the management of information are traditionally based in case studies of large companies and are driven by sophisticated electronic information systems. An alternative approach to identify and analyse information is adopted for small manufacturing companies, for a richer exploration of both informal and formal information. The process of data collection is explained in depth, and the findings illustrated in a conceptual model. The nature of information is discussed, showing that there are two dimensions - activities and interpretations. The findings show that information is highly systemic, and requires a qualitative, flexible approach to identifying and understanding it. The final outcomes show that informal information maintains flexibility, but there is an increasing need to support this with formal information, for traceability. The management of an information culture is crucial to this, manifested in the behaviour of people. Most significantly, it shows that there is a contention between the prevailing power culture and the uncertain and complex customer demands, and these factors sometimes prevent the effective management of information behaviour. The research explores a previously overlooked aspect of small companies - the apparent chaos and informality they operate in every day, and the vital contribution that this may play in their survival in the growing knowledge economy.